A conservative approach toward restoration of fractured anterior tooth - Puneet Goenka; Aditi Sarawgi; Samir Dutta (Wolters Kluwer Medknow Publications, 2012)
Reattachment of the fractured anterior tooth is a highly conservative and aesthetic treatment that has gained popularity in the recent past. Presented here is one such case in which a combination of external enamel bevel and internal dentinal groove has been used to enhance the bonding between the fractured fragment and the remaining tooth. The treatment was found to be successful both functionally and aesthetically at the 18-month follow-up.